2008
DOI: 10.1172/jci33777
|View full text |Cite
|
Sign up to set email alerts
|

Seven mutations in the human insulin gene linked to permanent neonatal/infancy-onset diabetes mellitus

Abstract: Permanent neonatal diabetes mellitus (PNDM) is a rare disorder usually presenting within 6 months of birth.Although several genes have been linked to this disorder, in almost half the cases documented in Italy, the genetic cause remains unknown. Because the Akita mouse bearing a mutation in the Ins2 gene exhibits PNDM associated with pancreatic β cell apoptosis, we sequenced the human insulin gene in PNDM subjects with unidentified mutations. We discovered 7 heterozygous mutations in 10 unrelated probands. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
245
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(262 citation statements)
references
References 47 publications
14
245
0
3
Order By: Relevance
“…Nevertheless, the patient bearing the mutation in the signal peptide shows a milder clinical course, and we cannot exclude that S Signal23 preproinsulin may be partially processed and secreted. Present knowledge indicates that insulin mutations with a proteotoxic effect cause apoptosis of the pancreatic ␤-cell (1), a process that in most patients takes several months after birth (1)(2)(3) (1-4) were diagnosed within the first 4 weeks of birth (i.e., the time interval still in use to define the neonatal period); most of them (more than 40) were diagnosed in the first year of life (infancy). Thus, we believe that classifying these patients as having permanent neonatal diabetes is misleading and that this term should be abandoned in favor of the term "monogenic diabetes of infancy," as previously suggested by our group (1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, the patient bearing the mutation in the signal peptide shows a milder clinical course, and we cannot exclude that S Signal23 preproinsulin may be partially processed and secreted. Present knowledge indicates that insulin mutations with a proteotoxic effect cause apoptosis of the pancreatic ␤-cell (1), a process that in most patients takes several months after birth (1)(2)(3) (1-4) were diagnosed within the first 4 weeks of birth (i.e., the time interval still in use to define the neonatal period); most of them (more than 40) were diagnosed in the first year of life (infancy). Thus, we believe that classifying these patients as having permanent neonatal diabetes is misleading and that this term should be abandoned in favor of the term "monogenic diabetes of infancy," as previously suggested by our group (1).…”
Section: Methodsmentioning
confidence: 99%
“…Present knowledge indicates that insulin mutations with a proteotoxic effect cause apoptosis of the pancreatic ␤-cell (1), a process that in most patients takes several months after birth (1)(2)(3) (1-4) were diagnosed within the first 4 weeks of birth (i.e., the time interval still in use to define the neonatal period); most of them (more than 40) were diagnosed in the first year of life (infancy). Thus, we believe that classifying these patients as having permanent neonatal diabetes is misleading and that this term should be abandoned in favor of the term "monogenic diabetes of infancy," as previously suggested by our group (1). Indeed, at least 12 patients with insulin gene mutations had the diagnosis of diabetes during childhood or adulthood (1-4 and this report), making the neonatal onset an exception.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first piece of evidence of the role of ERS in defective insulin secretion came from studies with monogenic forms of diabetes (148,149 was subsequently shown that the increased demand for insulin production in common forms of T2D could also impose perturbations in the ER, leading to the activation of the UPR (150,151). Furthermore, as in other tissues (147), FFAs can act as a trigger of ERS in pancreatic islets, acting in concert with high glucose (19,152).…”
Section: Metabolic Inflammation and Pancreatic Islet Dysfunction In T2dmentioning
confidence: 99%